2014
DOI: 10.7556/jaoa.2014.184
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Triage-Based Use of the Ottawa Foot and Ankle Rules on the Number of Orders for Radiographic Imaging

Abstract: There was no statistical evidence that application of the OFARs decreases the number of imaging orders or decreases LOS. This observation suggests that even when clinicians are being observed and instructed to use clinical decision rules, their evaluation bias tends toward recommendations for testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 24 publications
0
15
0
4
Order By: Relevance
“…Stiell et al 10 and Ashurst et al 11 concluded that the application of the Ottawa Protocol in emergency care resulted in a shorter time of care for these patients in relation to those who underwent radiography (80 min/116 min according to Stiell). Both studies also conclude that there was no significant difference in the degree of satisfaction of patients when not submitted to imaging tests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stiell et al 10 and Ashurst et al 11 concluded that the application of the Ottawa Protocol in emergency care resulted in a shorter time of care for these patients in relation to those who underwent radiography (80 min/116 min according to Stiell). Both studies also conclude that there was no significant difference in the degree of satisfaction of patients when not submitted to imaging tests.…”
Section: Discussionmentioning
confidence: 99%
“…Stiell et al 10 e Ashurst et al 11 concluíram que a aplicação do Protocolo de Ottawa no atendimento de urgência/emergência acarretou em um menor tempo de atendimento destes pacientes em relação aos que foram submetidos à radiografia, 80 min/116 minute segundo Stiell. Ambos os estudos também concluem que não houve diferença significativa no grau de satisfação dos pacientes quando não submetidos a exames de imagens.…”
Section: Discussionunclassified
“…Les articles retenusp r é sentaientd ifférents devisd e recherche, dontune revue systématique de la littératureet trois essais cliniques randomisés( tableau I). La majorité des articles sélectionnés étaient rédigéspard es auteurs nord-américains :neuf articles étaient américains [17][18][19][20][21][22][23][24] et cinq étaient canadiens [25][26][27][28][29][30]. Les autres articles étaient issus de la Chine [31],del' A ustralie [32][33][34], de la Suède [35], des Pays-Bas [36] et de Singapour [37].…”
Section: Caractéristiques Méthodologiques Des Articlesunclassified
“…Les radiographies pourdes traumatismes orthopédiques principalement de la cheville et du pied, ont étéé tudiées dans cinq publications [17,22,26,27,34]. Les ordonnances collectivesp ermettant la prescription et l'administration de médicaments par l'infirmière au triage ont étéétudiées dans 12 articles.…”
Section: Les Ordonnances Collectives éTudiéesunclassified
See 1 more Smart Citation